(Azido-κN){(E)-2-[1-(pyridin-2-yl)ethylideneamino]phenolato-κ3N,N′,O}copper(II) - Shiann-Cherng Sheu; Jui-Hsien Huang; Jack K. Clegg; Amitabha Datta (Acta Crystallographica Section E, 2013)
In the title complex, [Cu(C13H11N2O)(N3)], the CuII cation is four-coordinated by an N2O donor set of the tridentate Schiff base ligand and by the terminal N atom of the azide anion, forming a slightly distorted square-planar configuration.